2013
DOI: 10.1016/j.pain.2012.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite concentrations in the anterior cingulate cortex predict high neuropathic pain impact after spinal cord injury

Abstract: Persistent pain is a common reason for reduced quality of life after a spinal cord injury (SCI). Biomarkers of neuropathic pain may facilitate translational research and the understanding of underlying mechanisms. Research suggests that pain and affective distress are anatomically and functionally integrated in the anterior cingulate cortex and can modulate sensory and affective aspects of pain. We hypothesized that severe neuropathic pain with a significant psychosocial impact would be associated with metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 57 publications
6
68
1
Order By: Relevance
“…Alterations in structure and function in these areas14, 18, 55, 56 have been associated with impaired sensory processing and sensory discomfort in patients with SCI 22. Similar to findings in the spinal cord, myelin‐sensitive R1 and MT paralleled the volumetric changes observed in the thalamus, cerebellum, and medulla oblongata comprising the dorsal columns.…”
Section: Discussionsupporting
confidence: 53%
“…Alterations in structure and function in these areas14, 18, 55, 56 have been associated with impaired sensory processing and sensory discomfort in patients with SCI 22. Similar to findings in the spinal cord, myelin‐sensitive R1 and MT paralleled the volumetric changes observed in the thalamus, cerebellum, and medulla oblongata comprising the dorsal columns.…”
Section: Discussionsupporting
confidence: 53%
“…99 This alteration was not present in those with spinal cord injury without pain or with less severe pain, and provides evidence that proliferation of glia and glial activation within the cortex may contribute to the maintenance of neuropathic pain.…”
mentioning
confidence: 74%
“…One caveat that should be mentioned is that most of these studies have not taken patient comorbidities into account and some have revealed structural changes in non-neuromatrix regions, so such reorganisation may not always be pain-specific. 91 Changes in concentration of specific brain metabolites have been demonstrated in neuromatrix regions of people with chronic low back pain, 92-95 CRPS, 96,97 spinal cord injury, 98,99 and post-herpetic neuralgia. 97 In fact, it was some of this early work using magnetic resonance spectroscopy that lead to the hypothesis that morphological changes may be present in the brain.…”
Section: Brainstem Regionsmentioning
confidence: 99%
See 2 more Smart Citations